Trends in Public Debt in India: Lessons from Greek Crisis?. (January 2017) - Bhattacharjee, Subhomoy; Das, Dakshita
Abstract: There is not much new in the divide in economic literature between fiscal and monetary policy; what is new post-2008 is the emergence of the role of money supply and that of public debt to prominence as the instrument of choice for central banks and the government treasury. To a large degree, money supply and public debt now eclipsed the central role variables such as tax and interest rates had played in the setting of economic policies in countries both developed and developing. While literature is evaluating how the change in the role of these stock parameters to that of policy variables will play out, this article takes up the more mundane task of examining only one of them, which is public debt in the context of India. We believe that there is a key reason to do so. The Indian government has not used public debt as an active policy tool, so far, even as several countries have begun to do so (Mohanty, 2012 ). Instead, it has held on to a general desideratum of the need to reduce it; borne out of the scare of the balance of payments crisis of 1991. But 25 years after the crisis, it is important to examine if there is a conscious understanding within the government for the need to measure and deploy public debt especially as the room for active deployment of other fiscal tools, namely taxation is circumscribed. By FY14 India's public debt (centre and states combined), as percentage of GDP, stood at 66.7 per cent; it was 70.6 per cent in FY09. For the sake of comparison, the world's most indebted countries include Greece, of course, with its general government net debt at 173 per cent of its GDP. Others in the top 20 include Italy, Egypt, Portugal, Spain, France, the United Kingdom, Japan and the United States of America. By current estimates, India does not rank amongst the most indebted countries of the world. But is the position, one of strength or of a passive arrival that offers little or no policy direction to the government? Moreover, this article also argues that in the absence of such direction, there has been a build-up of debt in the economy instead of a reduction. Most of that build-up has been sought to be balanced by recourse to non-tax revenue. As fresh options to tap non-tax revenue dry up, public debt could emerge as the new pressure point for the economy.